Analysis of the frequency of biological sample recollections as quality indicators in a clinical laboratory of Distrito Federal, Brazil - Natani L. Coriolano; Izabel Cristina R. Silva; Thaís A. C. Lamounier
ABSTRACT Introduction: Clinical laboratory results influence more than 60% of medical decisions, impacting on disease prevention, diagnosis, and treatment. The use of quality indicators (QIs) is fundamental for quality assurance, once it allows monitoring the process and directs the taking of corrective actions. Objective: Classify the biological sample recollection requests for QIs identification in a clinical laboratory of Distrito Federal, Brazil. Material and methods: Data about the requests made in the biennium 2013-2014 were gathered and analyzed. Results and discussion: Among the 304,361 samples received, 1,914 (0.62%) had a request for recollection made in accordance with laboratory criteria. Most orders originated in the pre-analytical phase (57.7%). The most frequent reason for sample rejection was result confirmation (40.7%), followed by insufficient sample (21.9%), coagulated sample (18.1%) and hemolyzed sample (11, 9%). The hematology sector was responsible for most recollection requests (43.6%), followed by the biochemistry (29%) and the immunology (25.7%) ones. The laboratory emergency department accounted for only 0.1%. Orders were mostly placed by the outpatient clinic (40.7%), emergency (30.4%), and internal medicine (12.4%) departments. The percentage of orders is low, but does not exclude the need to reach lower rates. Underreporting was detected in the emergency sector, which indicates need for improvement in information registration. Conclusion: The numbers mentioned were selected as IQs for the pre-analytical phase, serving as guidelines for future actions taken by the team.